2019
DOI: 10.2174/0929867325666180104150854
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Role For Lifestyle Interventions In Obsessive-Compulsive And Related Disorders?

Abstract: Many of the currently available treatments for obsessive-compulsive and related disorders (OCRDs) such as pharmacotherapy augmentation strategies, partial hospitalization programs, deep brain stimulation, and neurosurgery are efficacious for individuals suffering from more severe forms of these conditions. Unfortunately, the application of these treatments in milder forms of illness and subclinical samples, which affect a substantial portion of the population, is not justifiable by their costs (e.g. cognitiveb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF), a brain molecule positively associated with neuroplasticity, learning and mental well-being, may also be implicated in the relationship between lifestyle and compulsive behaviours (Fontenelle et al, 2018). OCD patients, regardless of treatment engagement status, have lower levels of BDNF compared to healthy controls (Fontenelle et al, 2012; Maina et al, 2010; Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain-derived neurotrophic factor (BDNF), a brain molecule positively associated with neuroplasticity, learning and mental well-being, may also be implicated in the relationship between lifestyle and compulsive behaviours (Fontenelle et al, 2018). OCD patients, regardless of treatment engagement status, have lower levels of BDNF compared to healthy controls (Fontenelle et al, 2012; Maina et al, 2010; Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of lifestyle and related interventions has traditionally been considered within a medical framework, due to the association between lifestyle and chronic disease outcomes, such as future cardiac events (Fontenelle et al, 2018). Yet, the impact of lifestyle on mental illness symptoms is a growing area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, in specific cases, treatment of schizotypal traits may help to decrease hoarding and alleviate mental contamination symptoms. Although preliminary evidence supports the use of serotonin reuptake inhibitors in people with obsessive-compulsive personality features (a construct that partially overlaps with compulsivity) ( Ansseau et al, 1991 ; Ekselius and von Knorring, 1998 ), there is also current interest in the efficacy lifestyle interventions that may be able to redirect patients compulsivity traits toward healthier behaviors ( Fontenelle et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To counter this, studies have shown that BDNF can be increased with high-intensity physical activity (66), stress management such as yoga and meditation (67), and dietary alterations such as the use of probiotics (68,69) and reduced consumption of refined sugar and processed foods (8,70). Although cognitive inflexibility and psychological stress are drivers of OCRD symptom severity, increasing BDNF through lifestyle interventions may, in turn, increase cognitive flexibility and resilience to stress.…”
Section: Could Lifestyle Interventions For Ocrds Be Linked By Common ...mentioning
confidence: 99%
“…With research across the broader field of psychiatry moving toward the creation of global guidelines for medical care and lifestyle medicine in mental illness (1,15,16), it is imperative that the field of lifestyle medicine for OCRDs is synthesized and moved forward to ensure appropriate care is being provided to OCRDs patients engaged in mental health systems. However, across a number of recent reviews and position statements (1,15), evidence for the use of lifestyle interventions for OCRDs is lacking (8). Although research suggests that lifestyle interventions may be useful in reducing symptoms of OCRDs as well as improving overall quality of life, no known research has systematically synthesized the effectiveness of lifestyle interventions across OCRDs as defined in the DSM-5 (6).…”
Section: Introductionmentioning
confidence: 99%